G16(P) Youth perspective on the 'sexuality education: lessons learned and future developments in the who european region' conference 2017. (12th March 2018) - Gray, M
Abstract : Background and aims: Comprehensive sex education is a successful intervention approach to improving the mental and physical health of children, and is a crucial factor in developing the ability of young people to exercise informed autonomy over their sexual and reproductive rights and wellbeing. It is also recognised as a safeguarding factor against child sexual exploitation. As a member of the Sheffield branch of the sex education charity Sexpression, and the FPA Youth Council, I was invited to join a youth delegation at the Sexuality Education conference to share a youth perspective on past successes and failures in the WHO European Region. Methods: Data was collected from research by WHO, and the United Nations Populations Fund amongst others, and qualitative information gathered through focus groups and fishbowl discussions with international delegates Results: Country representatives raised challenges such as misconceptions about sexuality education and a perceived drop in moral standards, questioning of the role of the school vs. parental education, political and religious resistance, and the feasibility of sustainable programmes. Presented were positive examples of primary school age targeted sex education programmes, and the use of technology to provide information to younger audiences. The youth delegation were given a chance to feed back their perspective on national and local education and health initiatives. They noted the use of 'jargon' and inaccessible language in education and services. The lack of representation from central Asia and other gender identities was highlighted. A key recommendation from the youth delegation is that organisations continue to not only invite youth participation at technical conferences, but also value their input as near-to-peer educators of young people. Outcome: The youth delegation formed an international alliance for sex education, and recommendations from the technical conference have been distributed to delegates' organisations to inform their future work providing education and sexual healthcare to young people. As an organisation working with an ever more diverse school age population Sexpression will endeavour to make all its teaching resources inclusive of all cultures, sexualities and identities.